2021
DOI: 10.3390/ijerph18041840
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Nonsuicidal Self-Injury with Quality of Life and Mental Disorders in Clinical Adolescents—A Network Approach

Abstract: Although earlier research has highlighted that psychiatric disorders significantly impair patients’ quality of life (QoL), few studies have examined the relationship between nonsuicidal self-injury (NSSI) and QoL. Our aim was to investigate whether QoL mediates the mental disorder–NSSI relationship, and to study the QoL ratings agreement of self and parents in a clinical population of adolescents. We involved 202 adolescents from Vadaskert Child Psychiatric Hospital and Outpatient Clinic, Budapest, aged 13–18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 105 publications
(174 reference statements)
1
19
0
3
Order By: Relevance
“…NSSI behaviors can also occur in different psychiatric syndromes, primarily in mood, personality, anxiety, and substance use disorders (Nitkowski & Petermann, 2011 ). In parallel, life satisfaction and global well-being are patently lower in NSSI samples (Gyori et al, 2021b ). A low level of subjective well-being is itself a risk factor for unhealthy emotion regulation (Verzeletti et al, 2016 ) and psychopathology (Grant et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…NSSI behaviors can also occur in different psychiatric syndromes, primarily in mood, personality, anxiety, and substance use disorders (Nitkowski & Petermann, 2011 ). In parallel, life satisfaction and global well-being are patently lower in NSSI samples (Gyori et al, 2021b ). A low level of subjective well-being is itself a risk factor for unhealthy emotion regulation (Verzeletti et al, 2016 ) and psychopathology (Grant et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear how daily habits influence biological pathways for health, some of which are related to the immune system or inflammatory markers and promote healthy cellular activity; however, the impact of health perception on health is less studied and yet highly relevant [ 5 ]. Clear examples of its importance for health and longevity include: health and well-being have been linked to self-harm attitudes in the adolescence [ 6 ]; detrimental lifestyles such as poor sleep [ 7 , 8 ] and unhealthy eating habits [ 9 ] negatively impact HRQoL through various underlying mechanisms; and, compared to participants with no impairment, those reporting deteriorated self-perceived health (SPH) saw a RR for mortality of 1.99 (95% CI: 1.64 to 2.42) [ 10 ]. Some researchers stress that in some instances, these effects are of significant magnitude and thus cannot be omitted from future research [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sum, our previous study, among others, revealed a triple-pathway model between attentive-disruptive disorders and suicidality: the association between the two variables were mediated by affective, psychotic, and anxiety disorders ( 5 , 8 , 9 , 21 ). Our first aim was to confirm these findings on a different sample.…”
Section: Introductionmentioning
confidence: 58%
“…According to the previous research of our group, Balazs et al ( 8 ) described that the symptoms of ADHD are associated with an increased risk for non-suicidal self-injury among adolescents, and affective and psychotic disorders and suicide mediated this relationship. Another study of our research group also found with a network approach that mood disorders, psychotic disorders and anxiety disorders mediated the path between attention/disruptive disorders and suicidality ( 21 ). Moreover, anxiety had the strongest association with ADHD ( 21 ).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation